STEEL STRUCTURES FOR SUSTAINABLE BUILDINGS: ENERGY EFFICIENCY AND ARCHITECTURAL AESTHETICS - Arief Perdana Putra; Agung Bayu Saputro; Wakyudi; Ghina Rizqandi Qurrota A'yun (Faculty of Science and Technology University of Pramita Indonesia, 2024)
Sustainable building design requires the integration of structural efficiency, energy performance, and architectural expression. Steel structure is widely regarded as a strategic construction system because of its high strength-to-weight ratio, fabrication precision, reuse potential, and capacity to create long-span spaces. This article analyzes the contribution of steel structure to sustainable buildings through energy efficiency and aesthetics. The study applies a descriptive-comparative approach based on secondary data, literature review, and document analysis of three representative building typologies: office, industrial, and public long-span buildings. The findings indicate that steel structure supports sustainability through material efficiency and circularity, while also enabling passive design strategies such as daylight penetration and cross ventilation. Comparative scoring yields average values of 4.56 for sustainability, 4.44 for energy efficiency, and 4.56 for aesthetics on a five-point scale. Steel structure is therefore not only a structural system, but also an architectural device that connects environmental performance and visual identity. The study proposes an integrative model linking material efficiency, energy performance, and architectural expression as a basis for sustainable building design